Recovery of carbon fiber from carbon fiber reinforced plastics using alkali molten hydroxide - Takaaki Wajima; Kazuki Yamashita (Scientific Reports)
Abstract High-strength carbon fibers were recovered by a new method, involving the decomposition of the thermosetting resin part of carbon fiber-reinforced plastic (CFRP) by heating it in a mixture of sodium hydroxide (NaOH) and potassium hydroxide (KOH). Alkali molten hydroxide was prepared by heating the mixture of NaOH and KOH at various ratios (NaOH: KOH = 1:0, 3:1, 1:1, 1:3, 0:1) at 400oC, and the CFRP was then heated with the aforementioned alkali molten hydroxide under a nitrogen atmosphere at 200–400oC for 0–90 min. Subsequently, the CFRP was washed with distilled water and filtered to recover the carbon fibers, and its tensile strength was estimated. Carbon fibers with higher strength can be recovered by heating the CFRP with an alkali molten hydroxide. As the temperature increased, the strength of the recovered carbon fiber decreased owing to the increase in gas generation caused by the decomposition of the thermosetting resin and carbon fiber in the molten hydroxide, such as H2 and CH4. KOH increase in the alkali molten hydroxide promoted decomposition of the resin, whereas the fiber was degraded. High-strength carbon fiber, nearly the same as virgin fiber, can be recovered at 200oC using the NaOH: KOH molten hydroxide at a ratio of 1:3.